The Potency of Alkaloid Derivates as Anti-Breast Cancer Candidates: In Silico Study - Renadi, Sedin; Pratita, Anindita Tri Kusuma; Mardianingrum, Richa; Ruswanto, Ruswanto (Syarif Hidayatullah State Islamic University, 2023)
Breast cancer is the most frequent malignancy in women worldwide. One of the target receptors for the treatment of breast cancer are estrogen, progesterone, and HER2 receptors. An alternative treatment using natural ingredients has been developed, one of which is alkaloid compounds. This study aims to determine the activity of alkaloid compounds as anti-breast cancer agents through an in-silico method. Virtual screening (AutoDock Vina), molecular docking (AutoDock Tools), molecular dynamics (Desmond), scanning Lipinski's rule of five, as well as pharmacokinetic and toxicity parameters, were performed. The results of virtual screening, molecular docking, and molecular dynamics show that the compounds daurisoline, solasodine, and sambutoxin have stable interactions with the HER2 receptor, with the lowest values of RMSD (Root Mean Square Deviation) and RMSF (Root Mean Square Fluctuation) compared to other compounds. Based on the results of the study conducted, it was shown that daurisoline, solasodine, and sambutoxin were predicted to be used as anti-HER2 candidates for the treatment of breast cancer.